Neuronal Wiring Receptors Dprs and DIPs Are GPI Anchored and This Modification Contributes to Their Cell Surface Organization. - Lobb-Rabe, M.; Nawrocka, W.I.; Zhang, R.; Ashley, J.; Carrillo, R.A.; Özkan, E. (eNeuro, 2024)
The Drosophila Dpr and DIP proteins belong to the immunoglobulin superfamily of cell surface proteins (CSPs). Their hetero- and homophilic interactions have been implicated in a variety of neuronal functions, including synaptic connectivity, cell survival, and axon fasciculation. However, the signaling pathways underlying these diverse functions are unknown. To gain insight into Dpr-DIP signaling, we sought to examine how these CSPs are associated with the membrane. Specifically, we asked whether Dprs and DIPs are integral membrane proteins or membrane anchored through the addition of glycosylphosphatidylinositol (GPI) linkage. We demonstrate that most Dprs and DIPs are GPI anchored to the membrane of insect cells and validate these findings for some family members in vivo using Drosophila larvae, where GPI anchor cleavage results in loss of surface labeling. Additionally, we show that GPI cleavage abrogates aggregation of insect cells expressing cognate Dpr-DIP partners. To test if the GPI anchor affects Dpr and DIP localization, we replaced it with a transmembrane domain and observed perturbation of subcellular localization on motor neurons and muscles. These data suggest that membrane anchoring of Dprs and DIPs through GPI linkage is required for localization and that Dpr-DIP intracellular signaling likely requires transmembrane coreceptors.